Turn-off Fluorescent Sensing of Energetic Materials using Protonic Acid doped Polyaniline: A Spectrochemical Mechanistic Approach - Patil, Veerabhadragouda B.; Ture, Satish A; Yelamaggad, Channabasaveshwar, V; Nadagouda, Mallikarjuna N; Venkataraman, Abbaraju (Wiley-VCH, 2021)
The trace detection of energetic materials (EMs) is a challenge due to the very low vapor pressure possessed by these compounds. Polyaniline (PAni) possesses variable oxidation and reduction states, which makes it strike different from other conducting polymers in understanding the mechanism of fluorophore-analyte interaction leads to the designing of selectivity and sensitivity of analytes; also, fluorophore as a sensing device. The present work is aimed at trace detection of some very prominent EMs; nitroarenes viz., 1,3,5-trinitroperhydro-1,3,5-triazine (RDX), trinitrotoluene (TNT); nitramines viz., hexanitrohexaazaisowurtzitane (CL-20) and nitro ester viz., pentaerithroltetraniterate (PETN) employing para-toluenesulfonic acid as a dopant for PAni nanofibers (P-PAni). The P-PAni helps overcome the dual difficulties of PAni, i.e., solubility and removal of pi stacking when dimethylformamide (DMF) is used as a solvent. P-PAni showed good quenching response and selectivity towards EMs, with the LOD being the best for CL-20 (0.717 mu M center dot L-1). The sensing studies further collaborated with the Cyclic Voltammetry, FTIR and Raman Spectroscopy studies gave a detailed understanding of the bipolaron-polaron transition mechanism accompanying the electron transfer process in the fluorescence quenching study.
Fluorescenční snímání energetických materiálů pomocí polyanilinu dopovaného protonovou kyselinou: Spektrochemicko- mechanistický přístup
Keywords: energetic materials; doped polyaniline; fluorescence quenching; cyclic voltammetry; limit of detection; energetické materiály; dopovaný polyanilin; zhášení fluorescence; cyklická voltametrie; mez detekce